Assessment of practices for controlling shallow valley-bottom gullies in the sub-humid Ethiopian Highlands - Addisie, Meseret B.; Langendoen, E.J.; Aynalem, D.W.; Ayele, Getaneh K.; Tilahun, Seifu A.; Schmitter, Petra S.; Mekuria, Wolde; Moges, M.M.; Steenhuis, Tammo S. (MDPI, 2018)
Rehabilitation of large valley bottom gullies in developing countries is hampered by high cost. Stopping head cuts at the time of initiation will prevent large gullies from forming and is affordable. However, research on practices to control shallow gully heads with local materials is limited. The objective of this research was therefore to identify cost-effective shallow gully head stabilization practices. The four-year study was conducted on 14 shallow gullies (<3 m deep) in the central Ethiopian highlands. Six gullies were used as a control. Heads in the remaining eight gullies were regraded to a 1:1 slope. Additional practices implemented were adding either riprap or vegetation or both on the regraded heads and stabilizing the gully bed downstream. Gully heads were enclosed by fencing to prohibit cattle access to the planted vegetation. The median yearly head retreat of the control gullies was 3.6 m a-1 with a maximum of 23 m a-1. Vegetative treatments without riprap prevented gully incision by trapping sediments but did not stop the upslope retreat. The gully heads protected by riprap did not erode. Regrading the slope and adding riprap was most effective in controlling gully head retreat, and with hay grown on the fenced-in areas around the practice, it was profitable for farmers.